A Study of Financial Literacy in College Students - Sugiharti, Harpa; Rahim, Sarah Aulia; Nugraha, Nugraha; Purnamasari, Imas; Mardiani, Rika (Jurnal Pendidikan Akuntansi & Keuangan, 2024)
This study aimed to determine the financial literacy level of students of the Faculty of Economics and Business Education at the Indonesian Education University. The research method used in this research is survey and descriptive research with a quantitative approach. This study has a population of 1.681 Faculty of Economics and Business Education students at the Universitas Pendidikan Indonesia class of 2021 and 2022. This research departs from the issue of the rampant use of fintech at a productive age without being accompanied by good financial literacy skills, and it impacts lousy credit cases. The results of this study indicate that students of the Faculty of Economics and Business Education at the University of Education Indonesia are at the middle literacy level or sufficiently literate with gender does not differentiate the level of financial literacy between women and men, the region of origin does not differentiate the quality of the literacy level of students both from Java Island and outside Java Island, and an increase in the level of financial literacy accompanies students with personal income from the lowest to the highest.